CT Findings of Incarcerated Diaphragmatic Hernia After Laparoscopic Roux-en-Y Gastric Bypass: A Rare Case Report - Ni Luh Putri Kresnasari; Putu Ayu Winda Wirastuti Giri; I Wayan Agus Murcahya (Glosains: Jurnal Sains Global Indonesia, 2026)
Background: Diaphragmatic hernia following laparoscopic Roux-en-Y gastric bypass (LRYGB) is a rare but life-threatening complication. Diagnosis is challenging due to non-specific symptoms, and delayed recognition may result in intestinal incarceration, strangulation, ischemia, and respiratory compromise. Computed tomography (CT) is the primary imaging modality for timely diagnosis and surgical planning. Objective: To report a case of incarcerated diaphragmatic hernia following LRYGB, highlighting the CT imaging findings, postoperative radiological follow-up, and the role of multidisciplinary management. Methods: Case report following CARE guidelines. Clinical, laboratory, and radiological data were obtained retrospectively from the medical record of a patient treated at Bali Hospital in April–May 2024. Imaging evaluation included non-contrast abdominal CT, serial chest radiographs, and postoperative thoracoabdominal CT. Results: A 59-year-old woman with a history of LRYGB (2019) developed acute epigastric pain and vomiting during hospitalization. Non-contrast CT revealed extensive herniation of the stomach, jejunum, ileum, mesenteric fat, and part of the spleen through the esophageal hiatus into the right hemithorax, resulting in significant pulmonary compression, leftward mediastinal shift, and obstructive ileus with suspected intestinal ischemia. Emergency laparotomy confirmed these findings, revealing dense adhesions. Postoperatively, CT demonstrated hemopneumothorax and bilateral pleural effusion, which were managed with chest drainage and video-assisted thoracoscopic surgery (VATS). Serial imaging confirmed successful hernia repair with no recurrence. Conclusion: Multidetector CT with multiplanar reconstruction is essential for rapid diagnosis, operative planning, and postoperative monitoring of incarcerated post-LRYGB diaphragmatic hernia. A multidisciplinary radiological–surgical approach is critical for optimal outcomes in this rare emergency.